Structure/Property Relationships of Partially Crosslinked Poly(butylene succinate). Issue 8 (23rd October 2012) - Ma, Piming; Ma, Zhe; Dong, Weifu; Zhang, Yong; Lemstra, Pieter Jan
Abstract PBS is partially crosslinked by using DCP as an initiator. A low gel fraction (<30 wt%) and low crosslink density of the partially crosslinked PBS are obtained at a DCP content of <0.5 wt%. Consequently, the partially crosslinked PBS retains both its processability and its crystallinity. The overall crystallization rate of the PBS is enhanced by partial crosslinking as evidenced by a considerable increase in crystallization temperature (Tc). Meanwhile, the mechanical properties of PBS are significantly improved by the partial crosslinking. The structure/property relationships of the partially crosslinked PBS are explored. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>